Type 2 Autoimmune Pancreatitis: Consensus and Controversies - Yoh Zen (Gut and Liver, 2022)
Autoimmune pancreatitis (AIP) has attracted much attention in the last two decades, and due to the diagnostic value of immunoglobulin G4 (IgG4), the number of cases diagnosed in clinical practice has markedly increased. However, in contrast to prototypic IgG4-related type 1 AIP, a minor subtype of AIP, referred to as type 2 AIP, is less widely known and has thus not yet been characterized in detail. Type 2 AIP is unrelated to IgG4 and is a completely distinct entity from type 1 AIP. One confusing factor is that the two types of AIP share patterns of clinical presentation (e.g., acute pancreatitis and painless jaundice) and imaging abnormalities (e.g., diffuse or segmental enlargement). Since there are currently no established serum markers, the diagnosis of type 2 AIP is highly challenging and requires the tissue confirmation of neutrophilic injury to the pancreatic ducts, a finding designated as a granulocytic epithelial lesion. Approximately one-third of cases are associated with inflammatory bowel disease, particularly ulcerative colitis; however, the pathological relationship between these two conditions has not yet been clarified. Unanswered questions relate to its pathophysiology, the potential development of a similar granulocytic injury in other organs, and the characteristics of pediatric cases. This review summarizes consensus and controversies surrounding type 2 AIP, with the aim of increasing awareness and highlighting the unmet needs of this underrecognized condition.